THE INFLUENCE OF LEADERSHIP AND EXAMPLE OF CHRISTIAN RELIGIOUS EDUCATION TEACHERS ON THE FORMATION OF STUDENT CHARACTER (International Journal of Environmental Sciences, 2025)
Christian religious education is considered one of the forms of education that can shape the character of students. Character is a collection of traits and values that are owned by individuals, and is useful if it is developed from childhood. Therefore, the successful formation of student character requires support from Christian religious education teachers who have good leadership and are exemplary. This research aims to analyze the effect of teacher dedication and Christian Education learning recitation methods on learning outcomes for class VII SMP Negeri 1 Rantauprapat Year 2024. The population in the study was 140 students, and 35 people were selected as a sample. Collecting data on the effect of teacher dedication and Christian Education learning recitation methods on learning outcomes for class VII SMP Negeri 1 Rantauprapat Year 2024 is a questionnaire. The influence of the teacher's dedication variable on learning outcomes (Y) is 66.3%. The magnitude of the influence between the variables of the Christian Education Learning Recitation Method on Learning Outcomes is 63.5%. The magnitude of the influence of the teacher's dedication variable and the Christian Education learning recitation method simultaneously (simultaneously) on the learning outcomes of Class VII SMP Negeri 1 Rantauprapat in 2024 is 68.5%.